Advocates and Law Enforcement: Study of the Role of Advocates in Spiritual Dimensional Law in Indonesia - Agiyanto, Ucuk; Absori; Surbakti, Natangsa; Raharjo, Trisno; Ikhwan, Afiful (International Journal of Psychosocial Rehabilitation, 2020)
After the reform, in Indonesia the existence of advocates is regulated in Law number 18 of 2003 concerning Advocates. A large number of judicial mafia and judicial corruption involving advocates has made law enforcement worse in Indonesia. This lack of legal morality has had a quite alarming effect, one of which is the crisis in law enforcement in Indonesia which can be said to be one of the impacts of the law enforcement paradigm in Indonesia which still relies on the type of continental legal tradition (the rule of law). The next problem is that cases involving corruption are often orientation to material profit becomes a lord who continues to be worshipped, advocates in their area to face capitalism is part of a collaborator in crime. Laws at present appear to be business opportunities, rather than to alleviate the suffering that continues to have an impact on various law enforcement institutions. The legal issue as this big business in the United States emerged as the phenomenon of "Megalawyering". Such legal practices are no longer pursuing legal matters, because they carry out two things at once, namely some laws and some business. In connection with these matters, advocates have to advance the ethics of their profession. Moreover, the advocate profession is the work of the noble caste, who defends the small people from the arbitrariness of the authorities. This fact provides an essential lesson that advocates need to gather in a joint alliance to protect religious values with a spiritual dimension. The purpose of writing this is to explain the role of advocates in law enforcement in Indonesia and also describe the concept of law enforcement with a spiritual dimension. This research is based on legal research conducted with a qualitative non-doctrinal approach. A philosophical approach then followed this manuscript because it was intended to explore spirituality that integrates science and religion. The data needed in this study will be collected in three ways, namely: through interviews, observation and literature study. Data that has been received and processed will be discussed using qualitative analysis methods.